The composition of pre-service teacher teams and children’s competencies in inclusive education. 20th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2023. "Education as a Hope in Uncertain Times" - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

Fostering students’ peer relationships through the classroom-based intervention FRIEND-SHIP. Education 3-13 - Hassani, S.; Jakob, K.; Schwab, S.; Hellmich, Frank; Löper, Marwin Felix; Görel, Gamze (International Journal of Primary, Elementary and Early Years Education.)
Keywords: Life-span and Life-course Studies; Education

Wer kooperiert besser mit wem? – Effekte des Team-Teachings von Lehramtsstudierenden auf die Kompetenzen von Kindern im (inklusiven) naturwissenschaftlichen Sachunterricht. Vortrag auf der Sektionstagung Empirische Bildungsforschung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF) und der Kommission Bildungsplanung, Bildungsorganisation und Bildungsrecht (KBBB). Thema: „Schule und Lehrkräfte. Bildung neu denken“. - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

Effekte eines universitären Trainings zur Lehrerkooperation auf die inklusionsbezogenen Selbstkonzepte von Lehramtsstudierenden. Vortrag auf der Sektionstagung Empirische Bildungsforschung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF) und der Kommission Bildungsplanung, Bildungsorganisation und Bildungsrecht (KBBB). Thema: „Schule und Lehrkräfte. Bildung neu denken“. - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Mathematikleistungen von Grundschulkindern im Zusammenhang mit dem von ihnen wahrgenommenen Feedback und ihren selbstbezogenen Kognitionen. Vortrag auf der Sektionstagung Empirische Bildungsforschung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF) und der Kommission Bildungsplanung, Bildungsorganisation und Bildungsrecht (KBBB). Thema: „Schule und Lehrkräfte. Bildung neu denken“ - Knickenberg, Margarita; Finke, Nils; Hellmich, Frank

Kompetenzentwicklung im inklusiven Unterricht (KinU) – eine internationale Perspektive - Albers, Timm; Filipiak, Agnes; Franzen, Katja; Hellmich, Frank (Grenzen.Gänge.Zwischen.Welten. Kontroversen – Entwicklungen – Perspektiven der Inklusionsforschung)

Qualifizierung von Studierenden des Grund- und Förderschullehramts für Inklusion in Schule und Unterricht - Franzen, Katja; Albers, Timm; Hellmich, Frank (Qualifizierung für Inklusion. Grundschule)
Inklusion ist als Thema aus dem deutschen Bildungssystem nicht mehr wegzudenken und trotzdem stellt sie weiterhin eine Herausforderung auf unterschiedlichen Ebenen dar. Die Qualifizierung der pädagogischen Fachkräfte ist dabei neben der Bereitstellung adäquater Rahmenbedingungen als ein besonders wichtiges Handlungsfeld zu betrachten. Die Bände der Reihe „Qualifizierung für Inklusion“ greifen den bestehenden Forschungs- und Entwicklungsbedarf auf und geben einen Überblick über die Ergebnisse der vom BMBF im Rahmen des Programms „Qualifzierung der pädagogischen Fachkräfte für inklusive Bildung“ geförderten Forschungsprojekte. Adressiert werden damit sowohl Wissenschaftler:innen als auch mit dem Themenfeld Inklusion befasste Personen und Institutionen der Aus-, Fort- und Weiterbildung, der Bildungsadministration und der Bildungspolitik. Der zweite Band der Reihe versammelt die Vorstellung von Projekten, Ergebnissen und Materialien, die sich dem Bildungsbereich der Grundschule zuordnen lassen. Die Reihe besteht aus drei weiteren Bänden, in denen die Ergebnisse zur Qualifizierung für Inklusion im Elementarbereich (Band 1), in der Sekundarstufe (Band 3) sowie in der Berufsschule, Hochschule und Erwachsenenbildung (Band 4) vorgestellt werden.

Primary School Principals’ Views on the Required Conditions for a Successful Implementation of Inclusive Education - Görel, Gamze; Hellmich, Frank (Australasian Journal of Special and Inclusive Education)
Abstract Following the United Nations Convention on the Rights of Persons With Disabilities, questions concerning the joint education of students with and without special educational needs remain to be answered. Currently, there is a need for knowledge about the necessary conditions for a successful implementation of inclusive education. Thus, the aim of the present study is to identify conditions for the implementation of inclusion that are seen as necessary by primary school principals. Therefore, 32 primary school principals were interviewed. The results of the interview study reveal that factors like personnel, financial and material resources as well as building infrastructure in primary schools are seen as important requirements for the successful realisation of inclusive education. Apart from that, the importance of attitudes towards inclusion and sociopolitical conditions for the realisation of inclusion became apparent. Further conditions, which are mentioned from the interviewed principals’ point of view, are related to teacher training, appropriate class sizes and, for example, opportunities for exchanging information. The results of the study indicate that there are essential obstacles as perceived by primary school principals that can impede the implementation of inclusion in primary schools.
Keywords: General Engineering

Qualität der Erfahrungen aus dem inklusiven Unterricht und Selbstwirksamkeitsüberzeugungen von Grundschullehrkräften - Franzen, Katja; Moschner, Barbara; Hellmich, Frank (Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung)

Adaptiver Unterricht in der (inklusiven) Grundschule aus der Perspektive von Lehrkräften - Löper, Marwin Felix; Hellmich, Frank (Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung)

FRIEND-SHIP Intervention Program – The Handbook - Aroni, Katerina; Toulia, Anastasia; Alves, Sílvia Regina Gonçalves; Hassani, Sepideh; Heidrich, Franziska Anna; Franzen, Katja; Görel, Gamze; Löper, Marwin Felix; Aguiar, Teresa; Silveira-Maia, Mónica; Sanches-Ferreira, Maria Manuela Pires Sanches; Hellmich, Frank; et al.

Kooperatives Unterrichten von Studierenden des Lehramts an Grund- und Förderschulen als Vorbereitung auf den inklusiven naturwissenschaftlichen Sachunterricht - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne (Qualifizierung für Inklusion. Grundschule)
Inklusion ist als Thema aus dem deutschen Bildungssystem nicht mehr wegzudenken und trotzdem stellt sie weiterhin eine Herausforderung auf unterschiedlichen Ebenen dar. Die Qualifizierung der pädagogischen Fachkräfte ist dabei neben der Bereitstellung adäquater Rahmenbedingungen als ein besonders wichtiges Handlungsfeld zu betrachten. Die Bände der Reihe „Qualifizierung für Inklusion“ greifen den bestehenden Forschungs- und Entwicklungsbedarf auf und geben einen Überblick über die Ergebnisse der vom BMBF im Rahmen des Programms „Qualifzierung der pädagogischen Fachkräfte für inklusive Bildung“ geförderten Forschungsprojekte. Adressiert werden damit sowohl Wissenschaftler:innen als auch mit dem Themenfeld Inklusion befasste Personen und Institutionen der Aus-, Fort- und Weiterbildung, der Bildungsadministration und der Bildungspolitik. Der zweite Band der Reihe versammelt die Vorstellung von Projekten, Ergebnissen und Materialien, die sich dem Bildungsbereich der Grundschule zuordnen lassen. Die Reihe besteht aus drei weiteren Bänden, in denen die Ergebnisse zur Qualifizierung für Inklusion im Elementarbereich (Band 1), in der Sekundarstufe (Band 3) sowie in der Berufsschule, Hochschule und Erwachsenenbildung (Band 4) vorgestellt werden.

Effects of Teacher Feedback on Primary School Students’ Self-Efficacy Beliefs and their Interest in Science Lessons. Single Paper. ECER (European Conference on Educational Research) 2022 PLUS. “Education in a Changing World: The impact of global realities on the prospects and experiences of educational research” - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Pre-Service Teachers’ Collaborative Lesson Planning and their Self-Concepts in Inclusive Education. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Determinants for students’ attitudes towards peers with non-compliant classroom behavior in inclusive primary schools. Single Paper Presentation. AERA (American Educational Research Association) 2022. Annual Meeting Theme: „Cultivating Equitable Education Systems for the 21^st Century“, Roundtable Session: "Focus on Behavior in Special and Inclusive Education" - Löper, Marwin Felix; Lehofer, Mike; Schwab, Susanne; Hellmich, Frank

Do primary school students’ contact experiences matter for their attitudes towards peers with special needs? Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Löper, Marwin Felix; Lehofer, Mike; Schwab, Susanne; Hellmich, Frank

Primary school students’ social self-concepts, their empathy and their attitudes towards peers with social and emotional difficulties. Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Löper, Marwin Felix; Hellmich, Frank

Elementary school teachers' self-efficacy beliefs concerning inclusive education. Single Paper Presentation. AERA (American Educational Research Association) 2022. Annual Meeting Theme: „Cultivating Equitable Education Systems for the 21^st Century“ - Franzen, Katja; Moschner, Barbara; Hellmich, Frank

Primary school students’ attitudes towards peers with special educational needs – First findings of an intervention program for the promotion of students’ social participation. Symposium “Let’s be friends! The importance of social inclusion in the lives of children and adolescents” (Sepideh Hassani). ECER (European Conference on Educational Research) 2022 PLUS. “Education in a Changing World: The impact of global realities on the prospects and experiences of educational research” - Görel, Gamze; Löper, Marwin Felix; Hellmich, Frank

How to improve primary school students’ social participation in the inclusive classroom? – Preliminary results from an intervention study. Oral Communication. Symposium “FRIEND-SHIP: A school-based intervention aimed at improving students’ social participation implemented in four countries” (Sílvia Alves). Porto International Conference on Research in Education 2022 (ICRE 2022) - Görel, Gamze; Löper, Marwin Felix; Hellmich, Frank

The relationship between primary school students’ contact experiences and their attitudes towards peers with non-compliant behaviour. Single Paper. ECER (European Conference on Educational Research) 2022 PLUS. “Education in a Changing World: The impact of global realities on the prospects and experiences of educational research” - Löper, Marwin Felix; Lehofer, Mike; Schwab, Susanne; Hellmich, Frank

Teachers’ intentions to deal with heterogeneity in inclusive and non-inclusive primary schools. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Characteristics of good inclusive teaching from primary school teachers’ perspective. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Görel, Gamze; Franzen, Katja; Hellmich, Frank

Teachers’ experiences from teaching in (non-)inclusive primary schools and their behavioural intentions to manage heterogeneity. Oral Communication. Porto International Conference on Research in Education 2022 (ICRE 2022) - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Primary school teachers’ mastery experiences and their self-efficacy beliefs to teach in inclusive classrooms. Oral Communication. Porto International Conference on Research in Education 2022 (ICRE 2022) - Franzen, Katja; Moschner, Barbara; Hellmich, Frank

The importance of primary school teachers’ self-efficacy beliefs and their attitudes for their everyday practices in heterogeneous classrooms. Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Görel, Gamze; Löper, Marwin Felix; Hellmich, Frank

Elementary school teachers’ self-efficacy in inclusive education – An investigation of the associated sources. Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Franzen, Katja; Moschner, Barbara; Hellmich, Frank

How to explain primary school teachers’ self-efficacy to teach in inclusive classrooms. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Franzen, Katja; Moschner, Barbara; Hellmich, Frank

The importance of parental feedback for children’s reading motivation and their reading comprehension. Single Paper. 10th SELF International Conference. “SELF in Focus: Leading Research Perspectives and Applications in an Exciting New Age of Science” - Hellmich, Frank; Hoya, Fabian Karl

Effekte des Feedbacks von Lehrkräften auf die Selbstwirksamkeitsüberzeugungen und die intrinsische Motivation von Kindern im naturwissenschaftlichen Sachunterricht der Grundschule. Vortrag. 30. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE, Sektion Schulpädagogik). Thema: "Nachhaltige Bildung in der Grundschule" - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Pre-service teachers’ team-teaching practices and children’s competence development in inclusive schools. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

Effects of the composition of pre-service teacher teams on primary school students’ competencies in (non-)inclusive science lessons. Paper Presentation. EARLI SIG 15 Biennial Conference 2022 `Special Educational Needs´. “A Village to Teach a Child – The Influence of Contextual Factors on Learning and Development” - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

The composition of pre-service teacher teams and primary school students’ competencies in (non-)inclusive science lessons. Oral Communication. Porto International Conference on Research in Education 2022 (ICRE 2022), Polytechnic of Porto, Centre for Research and Innovation in Education (inED) of the School of Education - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

Determinants for primary school teachers’ inclusive practices in heterogenous classes. Paper Presentation. EARLI SIG 15 Biennial Conference 2022 `Special Educational Needs´. “A Village to Teach a Child – The Influence of Contextual Factors on Learning and Development” - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Quellen der Selbstwirksamkeitsüberzeugung von Grundschullehrkräften im Kontext inklusiver Erziehung und Bildung - Franzen, Katja

Erklärungsfaktoren für Handlungsintentionen von Lehrkräften an inklusiven und nicht-inklusiven Grundschulen bei der Gestaltung von adaptivem Unterricht. - Löper, Marwin Felix; Hellmich, Frank (Empirische Pädagogik)

The role of students’ experiences in attitude formation towards peers with non-compliant classroom behaviour in inclusive primary schools - Löper, Marwin Felix; Schwab, Susanne; Lehofer, Mike; Hellmich, Frank (European Journal of Special Needs Education)

Effects of pre-service teachers’ collaboration on children’s competencies and motivation in (non-)inclusive primary school science lessons - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva (International Journal of Inclusive Education)

Kompetenzentwicklung im inklusiven Unterricht (KinU) – eine internationale Perspektive - Albers, Timm; Filipiak, Agnes; Franzen, Katja; Hellmich, Frank (Grenzen. Gänge. Zwischen. Welten. Kontroversen – Entwicklungen – Perspektiven der Inklusionsforschung)

Kooperation von Lehrkräften im inklusiven Unterricht - Hoya, Fabian Karl; Hellmich, Frank (Empirische Pädagogik)

Kooperativ Forschen(d) lernen im inklusiven Sachunterricht der Primarstufe – Ein Theorie-Praxis verzahnter Ansatz zur Vorbereitung von Sachunterrichtsstudierenden auf das Praxissemester - Kirsch, Alexander; Blumberg, Eva; Hellmich, Frank; Hoya, Fabian Karl (Theorie und Praxis in der Lehrerbildung. Verhältnisbestimmungen aus der Perspektive von Fachdidaktiken)

Effects of teacher feedback on children’s self-concepts and motivation in science lessons. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

The role of teacher feedback for children’s self-concepts and motivation in primary school science lessons. Single Paper. ECER 2021 (European Conference on Educational Research). “Education and Society: expectations, prescriptions, reconciliations” - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Inklusionskompetenz von Lehramtsstudierenden im Vergleich dreier europäischer Bildungssysteme – Ergebnisse aus dem Forschungsprojekt. Vortrag. Abschlussveranstaltung der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF) - Albers, Timm; Filipiak, Agnes; Franzen, Katja; Hellmich, Frank

Inklusionskompetenz von Lehramtsstudierenden im Vergleich dreier europäischer Bildungssysteme –Schlussfolgerungen und Implikationen. Vortrag. Abschlussveranstaltung der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF) - Albers, Timm; Filipiak, Agnes; Franzen, Katja; Hellmich, Frank

Determinants for teachers’ intentions to manage heterogeneity in (non-)inclusive primary education. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Görel, Gamze; Löper, Marwin Felix; Hellmich, Frank

Primary school students’ contact experiences and their attitudes towards peers with disabilities. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Löper, Marwin Felix; Schwab, Susanne; Hellmich, Frank

Individual prerequisites for children’s attitudes towards peers with social-emotional disabilities. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Löper, Marwin Felix; Hellmich, Frank

The prediction of primary school teachers’ self-efficacy expectations in inclusive education. Single Paper. ECER 2021 (European Conference on Educational Research). “Education and Society: expectations, prescriptions, reconciliations” - Franzen, Katja; Moschner, Barbara; Hellmich, Frank

Primary school principals’ views on designing inclusive schools. 19th Biennial EARLI (European Association for Research on Learning and Instruction) Conference 2021. “Education and Citizenship: Learning and Instruction and the Shaping of Futures” - Görel, Gamze; Hellmich, Frank